THE EFFECT OF FUNDING DECISIONS ON FIRM VALUE WITH GOOD CORPORATE GOVERNANCE AS MODERATION VARIABLE - Natania Ratna Sari; Herman Ruslim (Jurnal Kontemporer Akuntansi, 2024)
The purpose of this study was to examine the effect of earnings management and funding decisions on firm value in the transportation sector companies in Indonesia. The moderating variable used is Good Corporate Governance which consists of the role of the Board of Commissioners, the intensity of Audit Committee meetings, Institutional Ownership and Managerial Ownership. This study used profitability as control variable. The data used as research material is secondary data originating from the financial reports of transportation companies that are listed on the Indonesia Stock Exchange in 2018-2020. The population and sample in this study got 57 company samples. The data analysis method used in this study is the regression test method. The results of the study show that funding decisions affect firm value. Meanwhile, real earnings management has no effect on firm value, and good corporate governance does not strengthen or weaken the effect of earnings management and decisions on firm value.